Kontribusi Taman Bacaan Masyarakat “Pondok Baca Puspita” di Kabupaten Wonosobo sebagai fasilitator belajar anak usia sekolah dasar - Rahmah, Tadzqiya Aulia; Ganggi, Roro Isyawati Permata (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. The people of Candi Hamlet, Wonosobo, are limited in accessing local libraries due to several factors. TBM “Pondok Baca Puspita” eventually became the strong foundation of the community in fulfilling information needs. This study discusses the contribution of TBM “Pondok Baca Puspita” as a means of learning for school children. Data Collection Methods. This is a descriptive qualitative research with the data collection techniques such as interviews, observation, literature study, and document analysis. Data Analysis. We used the interactive analysis model by Milles and Huberman's data analysis method. This involves data reduction, data presentation, and conclusion drawing. Results and Discussion. We identified several challenges in learning activities faced by elementary school-age children in Candi Hamlet, Wonosobo. They were low motivation to learn, economic limitations, and limited means of technology-based learning fulfillment. The contribution of TBM in providing learning facilities is shown in the Sedekah Ilmu Program, as a learning concept, which is a form of non-physical contribution. The provision of mobile phone was to assist in terms of physical contribution. TBM “Pondok Baca Puspita” collaborate with several parties to improve the services. Conclusion. TBM “Pondok Baca Puspita” contributes physically and non-physically in providing learning facilities for elementary school children in Candi Hamlet, Wonosobo.